274 A FLOATING HEART IN AN EXCAVATED CHEST. (15th December 2022) - Lodi, Elisa; Modena, Maria Grazia; Donati, Federica; Rodighiero, Eleonora; Lodi, Giovanni
Abstract: Pericardial effusion is a common finding in clinical practice either as incidental finding or manifestation of a systemic or cardiac disease. The spectrum of pericardial effusions ranges from mild asymptomatic effusions to cardiac tamponade. Etiology is one of the main factors determining patient's prognosis. However, in most cases the pericardial effusion, even if large, remains of unknown origin. Pectus excavatum (PEX) is a common deformity of the chest wall in which the inferior part of the sternum and the cartilage are displaced posteriorly. PEX is present within the first year of life in most affected children, more frequently in boys than girls. The chest deformity in PEX may lead to compression of the right-sided cavities between the sternum and the vertebral column impacting right ventricular anatomy and rendering cardiac assessment by echocardiography very difficult. The diagnosis of pericardial effusion is generally confirmed by echocardiography but determining its etiology may be difficult. Although many cases are idiopathic, a careful review of the patient's medical history, physical examination, and laboratory tests can reveal the etiology in most patients. The most common causes of pericardial effusion are infections, malignant tumors, connective tissue diseases, pericardial injury syndrome, myocardial pericardial disease, uremia. In the last years, an association between idiopathic pericardial effusion and PEX has been hypnotized. We report the cases of 2 athletes, 15 and 18 years old, who came to our attention for post COVID19 infection evaluation as indicated by ministerial "Return to Play" protocol. Physical examination was negative for any signs/symptoms. Resting ECG showed normal sinus rhythm. Stress test was performed and resulted negative for signs and symptoms of reduced coronary reserve and arrhythmias. The echocardiographic evaluation showed moderate-severe pericardial effusion, 20 mm and 18 mm, in the absence of hemodynamic alteration. Blood tests were performed (including CRP, ESR, blood count, D-Dimer, IL-6, uricemia) and resulted normal. CardioRM confirmed the presence of severe effusion without signs of hemodynamic impairment/instability. Holter-ECG, performed during training session, resulted negative for arrhythmic events. Athletes were followed up with six-monthly echocardiographic, HolterECG and stress test evaluations, with unchanged entity of the pericardial effusion and any arrythmia or symptoms at serial controls. Chronic pericardial effusion without active pericardial inflammation may represent a diagnostic and therapeutic challenge, especially in the later years as COVID-19 disease and vaccination may be associated with pericardial injury. In the last years, PEX has been associated with the finding of pericardial effusion. Although of interest, caution should be used before labeling indiscriminately a pericardial effusion as due to PEX, especially when clinical insights suggesting alternative diagnosis are present, such as neoplasm or tuberculosis, or when any signs of hemodynamic instability are present. On the contrary, when an otherwise idiopathic pericardial effusion is occasionally identified in a patient with PEX, both the patient and the referring physician may be reassured of the benign association of these two clinical entities, in the proper clinical setting.